2022
DOI: 10.1136/archdischild-2022-324593
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring during therapeutic hypothermia for hypoxic ischaemic encephalopathy: a feasibility study

Abstract: ObjectivesGlucose dysregulation is common in infants with hypoxic ischaemic encephalopathy (HIE) and is likely to exacerbate cerebral injury. Infrequent measurement of glucose concentrations makes both identification and prevention of this risk challenging. Continuous glucose monitoring (CGM) has the potential to address both these challenges, but has not been explored in these infants. We aimed to evaluate the feasibility and potential impact of real-time CGM in term infants with HIE being treated with therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Recently the use of continuous glucose monitoring has come to the fore in neonatology. Several studies have highlighted that this is a feasible adjunct to clinical care and may help to identify episodes of hypoglycaemia or hyperglycaemia, which would otherwise be clinically silent 9 29–31…”
Section: Discussionmentioning
confidence: 99%
“…Recently the use of continuous glucose monitoring has come to the fore in neonatology. Several studies have highlighted that this is a feasible adjunct to clinical care and may help to identify episodes of hypoglycaemia or hyperglycaemia, which would otherwise be clinically silent 9 29–31…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of CGM use as part of clinical decision making in HIE has not been explored, and needs to be preceded by validation of sensor accuracy during cooling. A recent study shows that CGM accuracy is comparable in normothermic and hypothermic conditions ( 31 ).…”
Section: What Types Of Neonates May Benefit?mentioning
confidence: 99%
“…Also, several studies have shown that initial dysglycemia has been detected in infants with neonatal encephalopathy. A few studies have suggested that hyperglycemia associated with HIE may affect brain microstructure and seizures [32][33][34][35]. It is also recognised that hypoglycemia is associated with neonatal brain injury [32,33,36].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…A few studies have suggested that hyperglycemia associated with HIE may affect brain microstructure and seizures [32][33][34][35]. It is also recognised that hypoglycemia is associated with neonatal brain injury [32,33,36]. Further research in this area is required to fully understand the role of dysglycemia in HIE.…”
Section: Glucose Metabolismmentioning
confidence: 99%